Law applicable to marriage property regimes in Regulation 2016/1103 of June 24, 2016. A technical and value analysis of the connecting factors - Calvo Caravaca, Alfonso-Luis; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The purpose of this study is to explore the system of connections to determine the Lawapplicable to the matrimonial property regime in Regulation (EU) 2016/1103 of the Council of June24, 2016 establishing reinforced cooperation in the field competition, applicable law, recognition and enforcement of resolutions in matrimonial property regimes. Not only are the connecting factors in theRegulation analyzed through a technical examination, but also using a value focused test. From a technicalpoint of view, some solutions could have been presented with greater transparency and coherence with other European regulations. On the contrary, from a value view, it should be highlighted that the connecting factors used lead to efficient, predictable and clear solutions that favour proper management of matrimonial assets in our current social scenario, in which the spouses frequently change their country of habitual residence and nationality and in which the assets linked to the matrimonial economy are usually scattered throughout several countries.